2019
DOI: 10.1002/jbt.22320
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of curcumin on biochemical and molecular changes in sodium arsenite‐induced oxidative damage in embryonic fibroblast cells

Abstract: The present study was aimed at determining the oxidative damage caused by sodium arsenite in 3T3 fibroblast cells and the possible protective role of curcumin (Cur) against sodium arsenite toxicity. Embryonic fibroblast cells were exposed to sodium arsenite (0.01, 0.1, 1, and 10 μM) in the presence and absence of Cur (2.5 μM) for 24 hours. Cell viability, cytotoxicity, lipid peroxidation, hydroxyl radical, hydrogen peroxide, antioxidant enzymes (superoxide dismutase, catalase, glutathione peroxidase, and gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Similar results were observed in embryonic fibroblasts coexposed to sodium arsenite and bioactive compounds from turmeric for 24 h, which evidenced increased cell viability and reduced oxidative stress in comparison with cultures only exposed to arsenite. Then, this study suggests that polyphenols can play a protective role in the presence of toxic agents [81].…”
Section: Discussionmentioning
confidence: 78%
“…Similar results were observed in embryonic fibroblasts coexposed to sodium arsenite and bioactive compounds from turmeric for 24 h, which evidenced increased cell viability and reduced oxidative stress in comparison with cultures only exposed to arsenite. Then, this study suggests that polyphenols can play a protective role in the presence of toxic agents [81].…”
Section: Discussionmentioning
confidence: 78%
“…NaAsO2 directly affects the antioxidant enzymes (SOD, Cat, GPx, and GST) and regulation of antioxidant genes (SOD1, Cat, and GPx1) in embryonic fibroblast cells and caused oxidative damage through increasing the cellular levels of hydrogen peroxide, hydroxyl radical and LPO. It has been found that CUR potentially improved antioxidant system genes and enzymes to defend the fibroblast cell toxicity created by NaAsO2 [214].…”
Section: 6other Arsenic Induced-pathologic Conditionsmentioning
confidence: 99%
“…Similar inconsistent conclusions also existed for the combined effects of curcumin and other heavy metals. Negligible protective effects of curcumin could be observed when combating the cytotoxicity elicited by As in embryonic fibroblast cells [ 34 ], however, curcumin was proved to decline the As-induced mortality rate by 40% in PC12 cells [ 35 ]. As a promising antidote with high efficiency and excellent biocompatibility, it is of great value to systematically evaluate the detoxification effect of curcumin against different typical heavy metals under the same experimental standards.…”
Section: Introductionmentioning
confidence: 99%